(untitled) (Journal of Academic Research, 2021)
In conventional network problems, it is assumed that decision maker is certain about the parameters (distance, time, …) between different nodes. But in real life situations, there always exist uncertainty about the parameters between different nodes. In this paper, we present algorithm for solving the fuzzy rough network problem, in this problem all parameters between different nodes are presented by triangular fuzzy rough numbers. By using the proposed algorithm a decision maker can obtain the optimal shortest path and optimal fuzzy rough shortest distance between source node and destination node. To illustrate algorithm a numerical example is solved and the obtained results are discussed